Do neighbours shape the tourism spending of rural households? Evidence from China - Jiafeng Gu (Current Issues in Tourism, 2023)
Previous studies on the determinants of household tourism expenditure have assumed that households independently determine their tourism expenditure. However, the possible influence of neighbours on tourism expenditure has been overlooked. This study is the first to apply spatial lag analysis to investigate the neighbour effect in the determination of rural household tourism expenditure. The results indicate that there is a significant neighbour effect on the tourism expenditure of rural households. This neighbour effect varies by region and by household head attributes. This paper suggests that the neighbour effect does help to explain household tourism consumption in rural areas.